Comparative Analysis of Inter-Island Carbon Emissions - Misdawita Misdawita; Any Widayatsari; Cut Endang Kurniasih (Newinera Publisher, 2026)
Carbon emissions are a major driver of global climate change, and Indonesia, as the world's fourth-largest archipelagic nation, faces significant challenges in managing its carbon footprint. The National Action Plan for Greenhouse Gas Emission Reduction allocates emission reduction targets to key sectors such as forestry and peatlands, agriculture, energy and transportation, industry, and waste management. Therefore, a thorough understanding of the comparison of carbon emissions across Indonesia's islands is crucial for designing more targeted and effective mitigation strategies to achieve national and global sustainability goals. This study analyzes the comparison of carbon emissions across six major Indonesian islands/regions: Java, Sumatra, Kalimantan, Sulawesi, Bali, Nusa Tenggara, and Maluku-Papua. The analysis was conducted on 43 economic sectors that contribute to direct CO₂ emissions. The primary objectives of this study were to identify differences in carbon emissions between islands and determine whether these differences are statistically significant, as well as to identify the unique characteristics of each island in its contribution to national emissions. The analysis revealed statistically significant differences in carbon emissions across islands in Indonesia. The analysis revealed extreme regional disparities in emission contributions. Java dominates, contributing 63.70% of total national emissions. Sumatra ranks second with 21.48%, while other islands contribute much less. The oil and gas mining sector contributes nearly a third of total national emissions, followed by the cement industry and electricity generation. This research makes an important contribution to understanding Indonesia's carbon emissions profile from a regional and sectoral perspective.